The effect of nicotinamide riboside injection concentrations on avian myogenesis - Anderson, Milea G.; Davis, S.; Gonzales, John M. (My University, 2019)
INTRODUCTION: The poultry industry strives to meet consumer demands. Murine studies indicated NR effects NAD+, mitochondria biogenesis, and ATP. Previous research found nicotinamide riboside (NR), a vitamin B3 precursor to NAD+, increased broiler embryo muscle mass when injected into the yolk at d10 of incubation. Cell proliferation is controlled by the MAPK/CDK pathway. OBJECTIVE: To evaluate the effect of in ovo injected NR concentration on pectoralis major (PM) weight, muscle fiber number, mitochondria content, and cyclin D mRNA expression. METHODS: Broiler eggs (N=120; Cobb 500) were weighed, incubated using standard conditions, and 100µl of 4 randomly assigned treatments (0.0, 2.5, 5.0, or 10.0 mM NR in 0.9% sterile saline) was injected into the yolk on incubation d10. Post-hatch, chicks were euthanized, left PM was weighed and removed for immunohistochemistry. Left quadricep muscles were removed for cytochrome c protein expression via Western Blotting and cyclin D mRNA expression by semi-quantitative real-time PCR. RESULTS: There were treatment effects for PM weight, muscle fiber number, and cyclin D3 mRNA expression (P<0.01). Embryos injected with 0.0 NR had lighter PM muscles than all other treatments (P<0.01, which did not differ from each other (P≥0.44). Embryos injected with 0.0 NR had the least amount of muscle fibers compared to all treatments (P<0.05), while 10.0 NR embryos had the most (P<0.01). Embryos injected with 2.5 and 5.0 did not differ (P=0.61). Embryos injected with 0.0 NR had greater D3 expression than all other treatments (P<0.04), which did not differ from each other (P>0.26). There were no treatment effects for cytochrome c protein, cyclin D1 or D2 gene expression (P≥0.53). CONCLUSION: The NR stimulated increase in muscle weight and fiber number was not due to mitochondria biogenesis. Cyclin D3 mRNA expression indicates this pathway may be downregulated due to increased number of fibers formed earlier during incubation.
Keywords: Spring 2019